An unusual catheter malposition following totally implantable venous access port insertion: The catheter tip located into the right axillary vein - Yüksel, Ahmet; Velioğlu, Yusuf; Demirel, Mustafa Enes; Uçaroğlu, Erhan Renan (Journal of Surgery and Medicine, 2019)
Totally implantable venous access port (TIVAP) devices have been used increasingly for repetitive chemotherapy administration, long-term parenteral nutrition, blood sampling and blood transfusion for last years. Several potential complications including catheter malposition can occur during the insertion of TIVAP devices. Catheter malposition is a less commonly reported and an important complication of TIVAP insertion. In this article, we presented an uncommon case report of catheter malposition following TIVAP insertion in a 47-year-old woman. To the best of our knowledge, this is the first reported case of mispositioned TIVAP where the tip of the catheter is in the right axillary vein.